Sensibilidade jurídica e embate colonial: análise do caso Saramaka Vs. Suriname / Legal sensibility and colonial struggle: an analysis on the Saramaka vs. Suriname case - Assis da Costa Oliveira (Revista Direito e Práxis)
Resumo O presente artigo analisa o caso povo Saramaka Vs. Estado do Suriname, julgado e monitorado pela Corte Interamericana de Direitos Humanos, com a seguinte estrutura: (1) apresentação do contexto histórico-cultural do caso; (2) reflexão sobre o papel do ativismo político-jurídico da Corte; (3) elaboração do resumo do caso Saramaka Vs. Suriname; (4) discussão das possíveis entradas da Antropologia no campo jurídico-judicial; (5) leitura do caso Saramaka Vs. Suriname pelo “olhar antropológico”. Palavras-Chave: Sensibilidade Jurídica; Direitos Indígenas; Antropologia do Direito; Direitos Humanos. Abstract This article analyze the case Saramaka People Vs. State of Suriname, judged and monitored by the Inter-American Court of Human Rights, with the following structure: (1) presentation of historical and cultural context of the case, (2) reflection on the political and legal activism of the Court, (3) preparation of the summary of the case Saramaka Vs. Suriname, (4) discussion of possible entries of Anthropology in the field legal-judicial, (5) reading of the case Saramaka Vs. Surinam with the " anthropological view”. Key-words: Legal Sensibility, Indigenous Rights, Anthropology of Law, Human Rights.